Optimal Forest Road Density as Decision-Making Factor in Wood Extraction - Simões, Danilo [UNESP]; Cavalcante, Felipe Soares [UNESP]; Lima, Roldão Carlos Andrade [UNESP]; Rocha, Qüinny Soares [UNESP]; Pereira, Gilberto [UNESP]; Miyajima, Ricardo Hideaki [UNESP] (My University, 2022)
Forest road construction projects mainly depend on factors related to terrain physiography, watershed, and wood harvesting. In the whole tree system, wood extraction is the activity most impacted by the density of forest roads, influencing the extraction distance. One of the alternatives is the optimal forest road density approach, which allows for the minimization of wood extraction costs and the optimization of the productive area. Given the above, the objective of this study was to analyze whether the optimal forest road density in areas of forests planted with eucalyptus allows for maximum productivity and the lowest cost of the road-wood extraction binomial in a whole tree system. The technical and economic analysis of wood extraction was based on the study of time, operational efficiency, productivity, and the cost of wood extraction with a grapple skidder. For the optimal forest road density, the cost of the wood extraction activity was considered, as well as the cost of construction, reconstruction, and maintenance of roads. In addition, the cost of a loss of productive area and the cost of excess forest roads were weighted. The optimal forest road density was 30.49 m ha−1 for an average extraction distance of 81.99 m, with the cost of loss of productive area of 0.49 USD m³ and the excess road of 80.19 m, which represented a cost of 978.31 USD ha−1. It is concluded that the optimal forest road density allows for the identification of excess forest roads, allowing for a reduction in the total cost for the implementation of roads. Therefore, it can be considered an essential variable in the planning of the forest road network, providing improvements in productivity and the costs of wood extraction with a grapple skidder.
Keywords: cost; forest roads; grapple skidder; productivity; wood harvesting